Barley and wheat beta-glucan content influenced by weather, fertilization, and genotype - Khaleghdoust, Banafsheh; Esmaeilzadeh-Salestani, Keyvan; Korge, Mailiis; Alaru, Maarika; Möll, Kaidi; Värnik, Rando; Koppel, Reine; Tamm, Ülle; Kurg, Max; Altosaar, Illimar; Loit, Evelin (Frontiers in Sustainable Food Systems, 2024)
Beta-glucan is one of the most important dietary fibers in cereal grains, having a great impact on human health and food quality. Wheat and barley are strategic crops and their fibers contribute towards their nutraceutical impact. However, the health of the environment is also important to ensure sustainable crop production. Hence the European decision makers have agreed to move towards organic cropping and to reduce the use of mineral fertilizers. Environment and agricultural management have a vast impact on the content of β-glucan in cereal grains. To exploit the valuable properties of β-glucan, the knowledge of factors increasing the amount of this component is crucial. We hypothesized that annual weather conditions, nitrogen fertilization, and cropping system affect the β-glucan amount in wheat and barley. For this purpose, spring barley and winter wheat flour samples from an eight-year-long period (2014 -2021) were characterized. The experiment included conventional and organic cropping systems with different nitrogen rates between 0 to 150 kg ha -1 . In addition, the variation of β-glucan content in different varieties was analyzed. The results showed that the content of β-glucan in barley and wheat grains was affected mainly by weather conditions not by fertilization. The latter finding means that the regulation of crop nutrition is not going to impact dietary fiber content in our everyday food. Lower temperatures during tillering and higher 1000 kernel weight and test weight showed a positive correlation with β-glucan content in barley grains, while precipitation during the grain filling period had a negative correlation. Our findings suggest that β-glucan can be obtained from low-input and organic systems as efficiently as from fertilized treatments. However, there is a need for adaptation strategies in industry, as β-glucan content can vary from year to year.